2022
DOI: 10.55782/ane-2022-016
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Achillea millefolium aqueous extract against oxidative stress and apoptosis induced by chronic morphine in rat hippocampal CA1 neurons

Abstract: Chronic opioid abuse can impair the hippocampal region of the brain. This study evaluates the neuroprotective effect of Achillea millefolium (Ach) on chronic morphine‑induced learning and memory impairment, oxidative stress, and neuronal apoptosis in the CA1 region of the rat hippocampus. Thirty‑two male Wistar rat rats were classified into four treatment groups (n=8). Morphine sulfate was administered chronically. The treatment groups were given Ach aqueous extract (100, 250, and 500 mg/kg), orally, each day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This paper demonstrated that the administration of morphine (5, 10 mg/kg) led to spatial memory impairment in mice, consistent with previous findings ( McNamara and Skelton, 1991 , Li et al, 2001 , Farahmandfar et al, 2010 , Khani et al, 2022 , Mozafari et al, 2022 ). Our data from the Y-maze test corroborated this notion, aligning with previous studies ( Castellano, 1975 , Ma et al, 2007 , Kitanaka et al, 2015 , Chen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…This paper demonstrated that the administration of morphine (5, 10 mg/kg) led to spatial memory impairment in mice, consistent with previous findings ( McNamara and Skelton, 1991 , Li et al, 2001 , Farahmandfar et al, 2010 , Khani et al, 2022 , Mozafari et al, 2022 ). Our data from the Y-maze test corroborated this notion, aligning with previous studies ( Castellano, 1975 , Ma et al, 2007 , Kitanaka et al, 2015 , Chen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…According to the conducted studies, Achillea millefolium L. is a biologically active plant that demonstrates multiple beneficial effects, including antioxidant, anti-inflammatory, spasmolytic, diaphoretic, hepatoprotective, choleretic, antipyretic, analgesic, antimicrobial and anticancer properties [ 18 , 19 , 20 ]. Achillea millefolium L. helps eliminate toxins from the body, controls bleeding, lowers blood pressure, relieves menstrual pain, and is used in the treatment of various diseases such as diabetes, tuberculosis, Alzheimer’s, and Parkinson’s disease [ 21 , 22 , 23 ]. Moreover, as indicated by Tilwani and coworkers, the yarrow-treated SARS-nCoV-2 cell exhibits the disintegration of the virus membrane [ 24 ].…”
mentioning
confidence: 99%